Taking the climate risk out of transplanted and direct seeded rice: Insights from dynamic simulation in Eastern India - Balwinder-Singh; McDonald, A.J.; Kumar, Virender; Poonia, S.P.; Srivastava, Amit K.; Malik, R.K. (Elsevier, 2019)
Rice productivity in Eastern Indo-Gangetic plains (EIGP) is extremely low, in part due to the prevailing practice of cultivating long-duration transplanted rice under rainfed conditions which leads to water stress and significant yield losses in many seasons. Rice establishment alternatives such as direct seeded rice (DSR) require less water at planting but also are accompanied by climate risks that constrain adoption. For both conventional transplanted and DSR systems, successfully addressing climate-based production risks may provide a strong basis for sustainable rice intensification in EIGP. In this ex ante study of rice yield and yield variability, the APSIM cropping system model was used to evaluate the efficacy of risk-reducing management practices in both transplanted and DSR systems. Simulations were conducted with 44 years (1970–2013) of historical weather data from central Bihar, India. Results confirm that the prevailing farmer practice of transplanting long-duration cultivars under rainfed conditions (fTR) often results in delayed transplanting and the use of older seedlings, leading to low (median 1.6 t ha−1) and variable (Standard deviation (SD) 2.1 t ha−1) rice yields. To improve the fTR system, simulations suggest that adoption of medium-duration hybrid rice (3.2 t ha−1), provision of supplemental post-establishment irrigation (3.2 t ha−1), or transplanting appropriately aged seedlings (3.4 t ha −1) can double yields as single interventions while, in the case of supplemental irrigation, significantly reducing inter-annual production variability. Additional gains are achievable when interventions are layered: supplemental irrigation paired with medium-duration hybrids increased median rice yields to 4.6 t ha−1 with much lower variability (SD 1.0 t ha−1). In these improved systems where irrigation is used to transplant the crop, simulations revealed the importance of timely planting: high and stable yields are achievable for long-duration cultivars when transplanting is completed by 2 August with this window of opportunity extending to 16 August for medium-duration hybrids. In rainfed DSR systems, the potential pay-offs from single interventions were even higher with medium-duration hybrids resulting in a median yield of 4.5 t ha-1 against 1.8 t ha−1 with long-duration cultivars. For irrigated DSR systems, an optimum sowing window of early to mid-June was identified which resulted in higher and more stable yields with lower water requirements. Simulation results suggest several risk-reducing intensification pathways that can be selectively matched to farmer risk preferences and investment capabilities within the target region in EIGP.